THE PERCEPTION OF INDIVIDUAL AND ORGANIZATIONAL CAREERS IN INCREASING THE ORGANIZATIONAL COMMITMENT - Rahmi Widyanti; Armanu Thoyib; Margono Setiawan; Solimun Solimun (Journal of Economics, Business, and Accountancy Ventura, 2012)
Organization commitment is very important for individuals working in any organization.Therefore, considering individuals and the perception toward the careers is really important.This study determines the direction of influence of basic individual careers and career developmentprograms on job satisfaction and organizational commitment. This research conducteda survey on Private Higher Education teaching staff of Kopertis (private higher educationcoordinator) Borneo in Banjarmasin. The data from 60 respondents were analyzedusing the Partial Least Square (PLS) to examine the relationship among variables basic individualcareers and career development programs that have a significant and positive impacton job satisfaction and organizational commitment. The results showed that the basic individualcareers and career development programs affect organizational commitment and jobsatisfaction. In addition, it is also proved that job satisfaction mediate the increasing organizationalcommitment.